2020
DOI: 10.1109/access.2020.3027361
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Scaling of Forest Aboveground Biomass Using Multi-Source Remote Sensing Data

Abstract: Accurate estimation of aboveground forest biomass (AGB) at a large scale is important in global carbon cycle, forest productivity, and climate change. Coarse resolution remote sensing data of long time series are often used to estimate large scale AGB, but the result is inaccurate due to the scaling effect caused by nonlinearity in data representation and the existence of mixed pixels containing different forest types and land uses. Improvement in the accuracy of AGB estimated from coarse resolution remote sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…(Lu et al, 2016). An approach based on structural analysis of mixed pixels and the random forest model was proposed by Wang & Jiao (2020), in order to increase the accuracy of AGB estimated from coarse resolution data in broadleaf forest, mixed forest, and some coniferous forests. The results showed that the accuracy of AGB estimated from MODIS data was increased using this method, and RMSE decreased from 51.6 Mg ha -1 to 26.8 Mg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…(Lu et al, 2016). An approach based on structural analysis of mixed pixels and the random forest model was proposed by Wang & Jiao (2020), in order to increase the accuracy of AGB estimated from coarse resolution data in broadleaf forest, mixed forest, and some coniferous forests. The results showed that the accuracy of AGB estimated from MODIS data was increased using this method, and RMSE decreased from 51.6 Mg ha -1 to 26.8 Mg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Multilayer perceptron neural networks were used to identify eight different types of forests based on the integrated dataset. The research in [30] proposed a novel method for aboveground biomass (AGB) estimation of forest based on the structural analysis of mixed pixels and the RF model. Specifically, a correction factor estimated from MODIS data was used to create a model that scales from fine-resolution data (SPOT 5) to coarse-resolution data (MODIS).…”
Section: A Multisource Remote Sensing Datamentioning
confidence: 99%
“…Remote sensing techniques have been widely used to estimate forest biomass and other forest inventory attributes, due to their ability to provide low-cost, accurate and timely results over large and impassable areas [11,12]. Various remote sensing data have been tested for forest biomass and carbon quantification, such as optical (e.g., multi-and hyperspectral) [13][14][15][16], synthetic aperture radar (SAR) [17][18][19], light detection and ranging (LiDAR) [20][21][22][23][24], and integrations between them [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral and SAR image analyse are the most common approaches for large-scale biomass estimation. However, signal saturation is the main limitation for both of them, especially over forested areas with complex topographies [12,30]. Unlike optical sensors, LiDAR signals can penetrate through the forest canopy, providing valuable vertical information about the forest structure [31].…”
Section: Introductionmentioning
confidence: 99%